Characteristics of splenic CD8+ T cell exhaustion in patients with hepatitis C. (8th September 2013) - Sumida, K.; Shimoda, S.; Iwasaka, S.; Hisamoto, S.; Kawanaka, H.; Akahoshi, T.; Ikegami, T.; Shirabe, K.; Shimono, N.; Maehara, Y.; Selmi, C.; Gershwin, M. E.; et al.
Summary There is increasing interest in the role of T cell exhaustion and it is well known that the natural history of chronic hepatitis C virus infection (HCV) is modulated by CD8+ T cell immunobiology. There are many pathways that alter the presence of exhaustive T cells and, in particular, they are functionally impaired by inhibitory receptors, such as programmed death‐1 (PD‐1) and T cell immunoglobulin and mucin domain‐containing protein 3 (Tim‐3). We obtained spleen, liver and peripheral blood (before and after splenectomy) lymphoid cells from 25 patients with HCV‐related cirrhosis undergoing liver transplantation for end‐stage disease or splenectomy for portal hypertension. In all samples we performed an extensive phenotypic study of exhaustion markers [PD‐1, Tim‐3, interferon (IFN)‐γ) and their ligands (PD‐L1, PD‐L2, galectin‐9] in CD8+ T cell subpopulations (both total and HCV‐specific) and in antigen‐presenting cells (APC; monocytes and dendritic cells). In the spleen, total and HCV‐specific CD8+ T cells demonstrated enhanced markers of exhaustion, predominantly in the effector memory subpopulation. Similarly, splenic APC over‐expressed inhibitory receptor ligands when compared to peripheral blood. Finally, when peripheral blood CD8+ T cells were compared before and after splenectomy, markers of exhaustion were reduced in splenic CD8+ T cells and APC. Our data in HCV‐related cirrhosis suggest that CD8+ T cells in the spleen manifest a significantly higher exhaustion compared to peripheral blood and may thus contribute to the failure to control HCV. Counteracting this process may contribute to inducing an effective immune response to HCV.